DRAMATURGY: DEVELOPMENT, STRUCTURE AND INFLUENCE ON MODERN SOCIETY (Intent Research Scientific Journal, 2023)
This research paper studies the history of drama, its features, theories and influence on modern society. The work analyzes various dramatic works and highlights the importance of dramatic elements in creating strong and emotionally rich plays. The study also examines the influence of dramaturgy on public opinion and culture, and compares traditional and modern forms of theatrical art.